Transformasional Leaderships Sebagai Gaya Kepemimpinan Strategis Masa Depan pada Satuan Polisi Sektor - Wahyu Eko Pujianto (Public Administration Dept, Faculty of Social and Political Science, 2022)
The purpose of this study is to analyze aspects of strategic leadership through transformational leadership in order to prepare future leadership. This study uses a qualitative approach with a qualitative descriptive type of research. Data collection techniques in this study using observation, documentation and interviews. Miles and Huberman argue that steps that can be taken to analyze data descriptively include data collection, reduction, and data presentation. The results of this study explain that transformational leadership is participatory leadership when leaders and followers work together to achieve a shared vision and mission. With the implementation of transformational leadership, it is hoped that the responsibilities of the Sector Police Chief will increase at the Gedangan Police Chief, Sedati Police Chief, Buduran Police Chief and Porong Police Chief. Furthermore, the Police Chief is expected to be able to provide motivation and be an inspiration for his members to work as a team to achieve the same goal. Not only being an officer who maintains security and order in the unitary area, but also being a friend to the local community. Finally, the research findings explain that the police chief must always be creative and innovate because the key to successful leadership is not being rigid in his choice of style, but moving between different styles according to the demands of the situation. It is the flexibility and adaptability that will differentiate one leader from another